Pemberdayaan Masyarakat melalui Pemanfaatan Tanaman Obat Keluarga (TOGA) di Pekon Blitarejo - Meidasetia, Vovi; Mulyati, Tri; Wahyuni, Annisa Tri; Aziza, Methia Kurniafi; Sari, Dwi Nila; Wasundari, Devia; Sisca, Sisca; Raihan, Muhammad; Purbasari, Salsa Embun; Dewi, Meli Puspita; Handayani, Dwi Putri; Handayani, Widia Putri; Maria, Okta; Valentina, Agnes; Anggraini, Evita (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The use of Family Medicinal Plants (TOGA) as a promotive and preventive effort in maintaining public health is still relatively low, especially in rural areas that have abundant natural resource potential, and this condition is exacerbated by high exposure to cigarette smoke in the household environment which risks causing various health problems, especially in the respiratory system. This community service activity aims to improve the knowledge, attitudes, and skills of the community in utilizing TOGA as an alternative to support family health, which was carried out in Dusun 02 Pekon Blitarejo, Gading Rejo District, Pringsewu Regency targeting teenagers and the general public. The methods used include counseling, training, and community mentoring, where counseling is carried out interactively using leaflets and posters, training through demonstrations of planting and processing herbal plants, and mentoring to ensure the sustainability of practices in the community environment. The results showed an increase in knowledge from 70% to 85% with an increase of 15%, as well as increased active community participation in planting and utilizing TOGA plants such as ginger, turmeric, lime, betel leaf, basil, and aloe vera.